Analysis of Factors Affecting ERP Implementation Performance Using the Analytical Hierarchy Process (AHP): A Case Study at PT Multi Makmur Investama (Multives) Tangerang - Roland Y.H. Silitonga; Alem Wandira Sembiring (The Indonesian Institute of Science and Technology Research, 2025)
The Indonesian packaging industry faces mounting pressure to align enterprise systems with evolving strategic and operational demands. This study investigates the performance of a mature Enterprise Resource Planning (ERP) system at PT Multi Makmur Investama (Multives), leveraging the Critical Success Factors (CSF) framework and Analytic Hierarchy Process (AHP) to identify and prioritize key determinants of ERP success. Ten CSFs were evaluated through expert pairwise comparisons and cross-validated via a perception survey of 51 ERP users. Results reveal ERP system quality (18.16%), top management support (14.19%), and user training (10.79%) as the most influential drivers. However, notable discrepancies emerged between expert prioritization and user satisfaction particularly in vendor support and training indicating underlying misalignments in long-term ERP usage. The study contributes a dual-layered evaluation model combining structured expert judgment and user-based validation, offering actionable insights for ERP optimization in emerging market contexts and extending theoretical discourse on ERP maturity evaluation.